Digitalisation as a form of modernisation - Smirnov, Victor E. (Journal of the Belarusian State University. Sociology, 2022)
The article substantiates the interpretation of digitalisation in post-Soviet countries as a form of modernisation on the basis of sociological and political economic approaches. Theoretical and practical approaches to the development of digital technologies in the West are considered. The prospects of digitalisation in the radical transformation of the economy and social order are revealed. It is proved that such a transformation is possible only if there are social forces ready to carry out this process. The political economic justification of the emergence and development of digitalisation in modern capitalist society is based on the idea of K. Marx about the expenditure of physical and nervous forces of the worker in the process of labour in the conditions of capitalist production. It is shown that from a political economic point of view, nervous activity has both the most important similarity with physical labour and a decisive difference from labour defined as universal. Unlike a person’s creative ability, this work can be measured by time. It is assumed that digital technologies imitate those aspects of human mental activity that can be interpreted as the expenditure of nervous forces. In this sense, an analogy is drawn between the industrial revolution of the past, which replaced the expenditure of physical forces by machines, and the digital revolution, in which the expenditure of nervous forces will be removed by the operation of digital devices.
Keywords: digitalisation; digital economy; social order; social forces; fakonomics; physical and nervous forces; modernisation